Diversidad genética de bananos y bananitos con microsatélites fluorescentes (2017)
Banana (Musa spp.) its fundamental to the economy of developing countries, including our country. Because of this reasons, the characterization of musaceas genetic diversity is essential to the management and exploitation of its genetic resources. In the current study 99 accessions from the collection of Musa spp. that are part of the germplasm bank of the Corporación Colombiana de Investigación Agropecuaria (AGROSAVIA, Palmira, Valle del Cauca), were evaluated by twelve fluorescent microsatellite molecular markers (SSR). A total of 206 alleles were identified, with a polymorphic information content (PIC) average of 0.106 and a marker index (IM) average of 1.377, indicating the presence of polymorphic and informative markers. The expected heterozygocity and number of alleles were superior in banana and ornamentals (He=0.836–Na=14.1 y He=0.848–Na=8.5, respectively), while bananitos presented inferior values (He=0.569–Na=6.25). The dissimilarity analysis allowed to identify possible duplicate accessions, given its identical genetic profile as: NATU08, NATU09, SABO03 y SABO01. Cluster and structure analysis identified three highly differentiated population groups, one formatted by bananitos, and the other two by banana of commercial cultivars and banana with wild characteristics plus ornamental ones. In conclusion, the collection presents a high genetic diversity mainly in the banana and ornamentals and in smaller amounts in bananitos; likewise, it is divided into discrete populations with high identity and low gene flow.